Androgens and prostate disease - Lori A Cooper (Asian Journal of Andrology, 2014)
A growing body of literature has established the anabolic benefi ts of testosterone (T) therapy in hypogonadal men. However, there remains a paucity of data regarding the risks of exogenous androgen use in older men and the potential for adverse effects on the prostate gland. Whether T therapy in older, hypogonadal men might worsen lower urinary tract symptoms or exacerbate, unmask, or even incite prostate cancer development has tempered enthusiasm for T therapy, while known prostatic disease has served as a relative contraindication to T therapy. Androgens are necessary for the development and maintenance of the prostate gland. However, epidemiologic studies do not consistently fi nd a positive relationship between endogenous serum androgen concentrations and the risk of prostate disease. Recent data demonstrate that 5α-reductase inhibitors decrease the risk of low-grade prostate cancer, suggesting that modifying androgen metabolism may have beneficial effects on prostate health, yet similar reductions in high-grade disease have not been observed, thereby questioning the true clinical benefits of these agents for chemoprevention. Knowing how to best investigate the relationship between androgens and the development of prostate disease given the lack of large, randomized trials is difficult. Accumulating data challenges the assumption that alterations in serum androgens have parallel effects within the prostate hormonal environment or change androgen-regulated processes within the gland. Long-term intervention studies are needed to truly ascertain the effects of androgen manipulation on prostate tissue and disease risk. However, available data do not support the notion that restoring serum androgens to normal physiologic ranges drives prostate disease.